2-sec-Butyl-1-(2-hydroxyethyl)-1H-benzimidazole-5-carboxylic acid - Hamzah, Nurasyikin; Ngah, Nurziana; Abd Hamid, Shafida; Abdul Rahim, Aisyah Saad (International Union of Crystallography, 2012)
In the title compound, C14H18N2O3, the carboxylic group is tilted by 12.00 (4)° with respect to the mean plane throught the benzimidazole ring system. The alcohol and carboxyl hydroxy groups are involved in intermolecular O-HO and O-HN hydrogen bonds, forming a two-dimensional network extending parallel the ab plane. The network is further stabilized by weak C-HO interactions. The sec-butyl group is disordered over two sets of sites with refined occupancies of 0.484 (4) and 0.516 (4).